AN OCULAR PROSTHESIS- A CASE REPORT - Shagun Acharya; Reecha Gupta; Paaras Kotwal; Monika Kotwal; Aditi Sharma; Udfer Hameed (IJRDO-Journal of Applied Science, 2025)
Ocular prostheses play a vital role in restoring the appearance and functionality of the eye for individuals who have suffered from eye loss due to trauma, surgery, tumors, or congenital eye defects. This case report presents the successful fabrication and fitting of a custom-made ocular prosthesis for a patient with an eye defect. The process involved careful examination and digital imaging for the fabrication of prostheses. The custom prosthesis provided an excellent aesthetic match, improved comfort, and enhanced the patient's self-confidence, ultimately leading to an improved quality of life.